Security enhancement of double random phase encoding using rear-mounted phase masking. (February 2018) - Chen, Junxin; Zhang, Yu; Li, Jinchang; Zhang, Li-bo
Highlights: Cryptanalysis of DRPE and its variants is synthetically and contrastively reviewed. The most critical issue for cryptanalysis of DRPE and its variants is found out. An improvement of DRPE is proposed, by a rear-mounted phase masking procedure. Experimental results have been given for validating the security performance. Abstract: In this paper, a security enhancement for double random phase encoding (DRPE) by introducing a rear-mounted phase masking procedure is presented. Based on exhaustively studying the cryptanalysis achievements of DRPE and its variants, invalidation of the second lens, which plays a critical role in cryptanalyzing processes, is concluded. The improved system can exploit the security potential of the second lens and consequently strengthen the security of DRPE. Experimental results and security analyses are presented in detail to demonstrate the security potential of the proposed cryptosystem.